Exchange Rate Assessments : CGER Methodologies - Ricci, Luca (International Monetary Fund, 2009)
The rapid increase in international trade and financial integration over the past decade and the growing importance of emerging markets in world trade and GDP have inspired the IMF to place stronger emphasis on multilateral surveillance, macro-financial linkages, and the implications of globalization. The IMF's Consultative Group on Exchange Rate Issues (CGER)--formed in the mid-1990s to provide exchange rate assessments for a number of advanced economies from a multilateral perspective--has therefore broadened its mandate to cover both key advanced economies and major emerging market economies. This Occasional Paper summarizes the methodologies that underpin the expanded analysis.